2004
DOI: 10.1541/ieejfms.124.461
|View full text |Cite
|
Sign up to set email alerts
|

Micro Electron Bunch Acceleration and Trapping by Intense Short Laser Pulse in Vacuum

Abstract: We propose an electron bunch acceleration and trapping mechanism by an intense short laser pulse in vacuum. By using a short laser pulse obtained by the linear combination of a TEM 10 mode and a TEM 01 mode with the same amplitude and the relative phase shift of π/2, the electrons are accelerated in the longitudinal direction by a longitudinal ponderomotive force, and the electrons divergence in the transverse direction can be suppressed by a transverse ponderomotive force. In order to analyze the electron mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…When the intense short-pulse laser composed of the TEM 10 +TEM 01 mode illuminates pre-accelerated electrons in vacuum, the pre-accelerated electrons are confined by the transverse ponderomotive force transversely and at the same time the laser longitudinal electric field generated by the transverse laser field gradient accelerates the electrons in the longitudinal direction. In our recent researches (13)- (15) , we found a high-energy electron bunches are generated by the TEM 10 +TEM 01 mode laser. This paper presents that under appropriate conditions of the TEM 10 +TEM 01 mode laser and the pre-accelerated electrons, the longitudinal laser electric field compresses the pre-accelerated electrons in the longitudinal direction into an attosecond pulse from an initial size of a few hundreds femtoseconds; the high-density short-pulse electron bunch generation depends especially on the pre-accelerated electron initial energy, and we found that there is the optimal electron initial energy.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…When the intense short-pulse laser composed of the TEM 10 +TEM 01 mode illuminates pre-accelerated electrons in vacuum, the pre-accelerated electrons are confined by the transverse ponderomotive force transversely and at the same time the laser longitudinal electric field generated by the transverse laser field gradient accelerates the electrons in the longitudinal direction. In our recent researches (13)- (15) , we found a high-energy electron bunches are generated by the TEM 10 +TEM 01 mode laser. This paper presents that under appropriate conditions of the TEM 10 +TEM 01 mode laser and the pre-accelerated electrons, the longitudinal laser electric field compresses the pre-accelerated electrons in the longitudinal direction into an attosecond pulse from an initial size of a few hundreds femtoseconds; the high-density short-pulse electron bunch generation depends especially on the pre-accelerated electron initial energy, and we found that there is the optimal electron initial energy.…”
Section: Introductionmentioning
confidence: 95%
“…Here we present a new method of a generation of a high-density attosecond electron bunch by the TEM 10 +TEM 01 mode laser in vacuum. In direct electron acceleration in vacuum, it was difficult to produce high-density electron bunches, because the laser transverse ponderomotive force scatters the electrons in the perpendicular direction of the laser propagation (10)- (15) . This electron density reduction can be suppressed by a laser composed of a linear combination of the Hermite-Gaussian TEM 10 and TEM 01 modes with the orthogonal polarization (13)- (15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation